Exposer les malades en dermatologie. Moulage et disponibilité de beaux cas à l’hôpital Saint-Louis (1801-1979) - Sophie Delpeux (Histoire, Médecine et Santé)
When the sculptor Jules Baretta created his first dermatological casts at the hôpital Saint-Louis around 1867, he introduced to the doctors of the institution a method that would finally be able to replicate the presence of patients and their conditions. This article examines how, both in the choice of diseases represented and in the decision to display them in an impressive museum, a lasting and problematic link is formed between the representation and exhibition of individuals. This serves not only the transmission of knowledge in the field of dermatology but also the pursuit of prestige.